Estimation of the wheel-rail lateral contact force through the analysis of the rail web bending strains. (March 2017) - Cortis, D.; Bruner, M.; Malavasi, G.; Rossi, S.; Catena, M.; Testa, M.
Highlights: Experimental approach to estimate the wheel-rail lateral contact force. Decoupling of effects of wheel-rail lateral forces from those of the vertical ones. Analysis of the bending strains in the cross plane of the rail web. Finite element simulations and laboratory tests of the measurement system. Identification of a coefficient by which it is possible estimate the lateral force. Abstract: Vertical overloads and imbalances in the composition of a railway vehicle can result in damage to the track and in a non-conformity regarding safety of operation. On the other hand, wheel-rail lateral contact forces are more directly involved in the running safety and deserve a special focus. In this paper, an experimental approach to estimate lateral forces applied by rolling stock to the track is presented. The method is based on the analysis of bending strains in the cross plane of the rail web. This approach allows the decoupling of effects of the lateral force from those of the vertical one with a simple combination of bending stresses measured on the rail web. The research uses finite element simulations and laboratory tests. The numerical and experimental results have identified an independent coefficient from the applied loads by which it is possible estimate the magnitude of the lateral force.